Espaço e lugar: uma análise fenomenológica da percepção dos moradores de Janauari frente à dinâmica do turismo. - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The geography humanistic existential phenomenological bases underpinning the theoretical construction adopted by us in this work. Understanding the perception of residents Janauari front dynamics of tourism, as well as knowing the landscape of the place, and understand how residents perceive and represents, constitutes the research objectives. This work is important to think about the place beyond the perspectives of the physical elements, that is, but think of it in its complexity, where the physical and human elements are woven together in the same formation, which leads to the recovery of a way of life and a culture. We aimed to study Janauari as the place where men and women laid the foundation of his being, from experience, constituting the world lived the same. Besides reflecting the place from the existential relationship of its residents, this work has its importance, promote reflection about tourism who had not only viéis economistic this activity. This was understood by us as a phenomenon of human experience. Janauari, instead we have studied, belongs to the municipality of Iranduba, Amazonas state, about 25 km from Manaus, Janauari has based its economy tourism and crafts. The theoretical and methodological approach was phenomenological. Since this is a qualitative research was adopted as the methodological procedures oral history of life of the inhabitants and the development of Mind Maps. This study has helped understand a place that is not only rich in natural beauty, but mostly of men and women who built, rebuilt, recognize, identify and orient themselves as "people of the place." Through their experiences, represents the place where they underpinned their lives, they lived in a place, a place of human existence, called by all of Janauari.
Keywords: Geografia Humanista; Lugar; Janauari; Paisagem; Percepção; Turismo.; Humanistic Geography; Place; Janauari; Landscape; Perception; Tourism; CIÊNCIAS HUMANAS: GEOGRAFIA